2021
DOI: 10.18502/sjms.v16i2.9296
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Against Doctors in Khartoum State, Sudan, 2020

Abstract: Background: Workplace violence against healthcare workers and especially doctors are now clearly taken as a rapidly rising health problem in Sudan with great political and legal concerns. The current study was aimed at exploring the prevalence of verbal and physical workplace violence, the major factors associated with it, and its consequences reported by medical staff in Khartoum, Sudan government hospitals in 2020. Methods: This cross-sectional study utilized self-administered questionnaires to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
6
11
1
Order By: Relevance
“…M Elamin et al 2020 reported that 50% of respondents were victims of violence in the past year. Of the 92% were nonphysical, which is higher than our study gures if we consider nonphysical to be emotional (11). Different classi cations of violence could explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…M Elamin et al 2020 reported that 50% of respondents were victims of violence in the past year. Of the 92% were nonphysical, which is higher than our study gures if we consider nonphysical to be emotional (11). Different classi cations of violence could explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
“…The dependent signi cance was tested using a logistic regression model with a p-value < 0.05 aa s statistically signi cant value for the same pre-mentioned covariates. This method was adapted from Elamin's research (11). All methods were carried out by relevant guidelines and regulations.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, there is still paucity of research [58]. In a crosssectional study carried out in 2020 in Sudan [59], 50% of doctors reported they had been victims of some form of violence (mainly verbal violence and, as for other countries, among younger doctors). A Nigerian study showed similar findings among physicians in general [60] while the prevalence of physical violence against mental health professionals showed that 33% of the doctors report physical assaults in the previous 12 months and 73% in their whole career [61].…”
Section: Africamentioning
confidence: 99%
“…A new law was approved by the transitional government in Sudan on May 25th, 2020, that stipulates "verbal or physical abuse of medical professionals, disrupting work or destroying assets in medical facilities, and publishing incorrect information that affects the performance of medical personnel can be punishable with imprisonment for up to 10 years" [13]. WPV to the HCWs has an impact on their psychological state and work performance and results in demotivation, poor job satisfaction, and early physician burnout [14][15][16]. Furthermore, it has been linked to a higher risk of suffering post-traumatic stress disorder, anxiety, and depression [17,18].…”
Section: Introductionmentioning
confidence: 99%